GT Repeats Are Associated with Recombination on Human Chromosome 22 - Majewski, Jacek; Ott, Jurg

(untitled) (Genome Research, 2000)
The rate of meiotic recombination is not a constant function of physical distance across chromosomes. This variation is manifested by recombination hot spots and cold spots, observed in all organisms ranging from bacteria to humans. It is generally believed that factors such as primary and secondary DNA sequence, as well as chromatin structure and associated proteins, influence the frequency of recombination within a specific region. Several such factors, for example repetitive sequences, gene promoters, or regions with the ability to adopt Z-DNA conformation, have been hypothesized to enhance recombination. However, apart from specific examples, no general trends of association between recombination rates and particular DNA sequence motifs have been reported. In this paper, we analyze the complete sequence data from human chromosome 22 and compare microsatellite repeat distributions with mitotic recombination patterns available from earlier genetic studies. We show significant correlation between long tandem GT repeats, which are known to form Z-DNA and interact with several components of the recombination machinery, and recombination hot spots on human chromosome 22.